THE INFLUENCE OF GREEN ACCOUNTING VARIABLES ON ENVIRONMENTAL PERFORMANCE - Kusiyah; Nurjanna Ladjin; Siti Aisyah; Tumija; Tri Widyastuti Ningsih (ITB AAS Indonesia Surakarta, 2025)
Abstract This study used five hundred respondents, namely five hundred employees of PT Perkebunan Nusantara I, II III, IV and VII spread throughout Indonesia with the category of working for more than one year as many as three hundred and fifty employees, working for more than three years as many as one hundred employees, and working for more than five years as many as fifty employees. The data distributed was collected first and analyzed using the smart PLS 4.0 analysis tool. Based on this, it can be concluded that this research is a quantitative research category with an expansive approach that relies on previous research, especially the three mentioned above to prove the hypothesis in this study. The result in this article show the Green Accounting variable can have a positive relationship direction and a significant influence on Environmental Performance. This can be caused by the P-Values ​​which are positive and below the significance level of 0.05, namely 0.002. The results of the third table mean that Environmental Accounting can make the company's finances stable, the mental and physical health of employees increases, and ultimately can improve the Company's Environmental Performance. It's just that the results in this study show that the Green Accounting variable on Environmental Performance is more significant than previous studies. Keywords : Green Accounting, Environmental Performance, Influence